Guilingji Protects Against Spermatogenesis Dysfunction From Oxidative Stress via Regulation of MAPK and Apoptotic Signaling Pathways in Immp2l Mutant Mice - Wang, Zhenqing; Xie, Yun; Chen, Haicheng; Yao, Jiahui; Lv, Linyan; Li, Yanqing; Deng, Chunhua; Zhang, Min; Sun, Xiangzhou; Liu, Guihua (Frontiers in Pharmacology, 2022)
Male infertility is a major health issue with an estimated prevalence of 4.2% of male infertility worldwide. Oxidative stress (OS) is one of the main causes of male infertility, which is characterized by excessive reactive oxygen species (ROS) or lack of antioxidants. Meanwhile, it is reported that oxidative stress plays an important role in the spermatogenic impairment in Inner mitochondrial membrane peptidase 2-like (Immp2l) mutant mice. In this study, we focused on the potential mechanism of Guilingji in protecting the spermatogenic functions in Immp2l mutant mice. The results revealed that Immp2l mutant mice exhibit impaired spermatogenesis and histology shows seminiferous tubules with reduced spermatogenic cells. After administration of Guilingji [150 mg/kg per day intragastric gavage], however, alleviated spermatogenesis impairment and reversed testis histopathological damage and reduced apoptosis. What’s more, western blotting and the levels of redox classic markers revealed that Guilingji can markedly reduce reactive oxygen species. Moreover, Guilingji treatment led to inhibition of the phosphorylation of mitogen-activated protein kinase (MAPK), regulated apoptosis in the cells. In summary, Guilingji can improve spermatogenesis in Immp2l mutant mice by regulating oxidation-antioxidant balance and MAPK pathway. Our data suggests that Guilingji may be a promising and effective antioxidant candidate for the treatment of male infertility.